APLIKASI KAJIAN SEMIOTIKA PADA TAFSIR AL-QUR’AN (KAJIAN INTERTEKSTUAL STUDI KASUS TAFSIR AL-IBRIZ LI-TARJUMANI MA’RIFATI TAFSIR AL-QUR’AN AL-‘AZIZ KARYA BISRI MUSTOFA DENGAN TAFSIR JALALAIN KARYA JALALUDDIN AL-MAHALLI DAN JALALUDDIN AS-SUYUTHI) - Lu’luatul Aisyiyyah; Dadan Rusmana (LP2M Universitas PTIQ Jakarta, 2023)
The purpose of this research is to understand the purpose of interpreters using several symbols in their interpretation. The Javanese language used in the interpretation is the language that is often used in the life of Islamic boarding schools and society. The symbols expressed by the interpreter aim to make the reader able to sort and understand them with the concepts presented by the interpreter. This research will be examined using a qualitative analysis of literature which will thoroughly discuss material related to the intertextual of al-Ibriz’s interpretation with Jalalain’s interpretation. Understanding will expand and mature if the existing theory is practiced into the verses of the Qur’an. So the researcher will try to explore the verses of the Qur’an which contain elements of faidah in juz 5 which are contained in three verses. The results of the research conducted illustrate that a manuscript text carries thoughts that existed in the past and then these thoughts are developed. Al-Ibriz's interpretation with its inherent Javanese provides several unique elements of culture which are applied in religious studies, especially in the field of interpretation.